Phase transitions in particle physics: results and perspectives from lattice Quantum Chromo-Dynamics - Aarts, Gert; Aichelin, Jörg; Allton, Chris; Athenodorou, Andreas; Bachtis, Dimitrios; Bonanno, Claudio; Brambilla, Nora; Bratkovskaya, Elena; Bruno, Mattia; Caselle, M.; Conti, Costanza; Contino, Roberto; et al. (Progress in particle and nuclear physics, 2023)
Phase transitions in a non-perturbative regime can be studied by ab initio Lattice Field Theory methods. The status and future research directions for LFT investigations of Quantum Chromo-Dynamics under extreme conditions are reviewed, including properties of hadrons and of the hypothesized QCD axion as inferred from QCD topology in different phases. We discuss phase transitions in strong interactions in an extended parameter space, and the possibility of model building for Dark Matter and Electro-Weak Symmetry Breaking. Methodological challenges are addressed as well, including new developments in Artificial Intelligence geared towards the identification of different phases and transitions.
Gesehen am 21.11.2023